Postgraduate Engineering Education in Canada: Responses to Industrial Needs - Kavanagh, Robert J. (Canadian Journal of Higher Education, 1986)
Postgraduate engineering education in Canada was relatively late in its development but has matured rapidly in recent years. In the course of this development there has been a gradual evolution of engineering postgraduate degree programs away from the science model and towards a structure which reflects the different orientation of engineering education and research. This paper reviews the development of postgraduate engineering education at Canadian universities and discusses some of the current issues facing engineering educators. The needs of Canadian industry for highly qualified engineering graduates are increasing as competition from other countries intensifies. The paper reviews and gives examples of actions which the universities, industry and governments have taken in order to improve the calibre of postgraduate engineering education in Canada and to respond to the needs of Canadian industry for highly qualified engineers.